Impact of Cultural Tourism upon Urban Economies: An Econometric Exercise - Elena Bellini; Ugo Gasparino; Barbara Del Corpo; William Malizia (Fondazione Eni Enrico Mattei (FEEM), 2007)
In recent years, interest in tourism has spread rapidly throughout many small and medium European cities, which previously have not necessarily considered themselves as tourist destinations. Tourism is increasingly seen as a potential lever towards high economic growth, measured both in terms of income and employment. In the present Working Paper we report the analysis on the economic impact undertaken in the framework of the PICTURE Project, showing the results of a novel econometric exercise to statistically assess the impacts of cultural tourism upon European municipalities. More precisely the analysis aims at estimating the effects of tourism specialisation on local income and prices. The Working Paper is built as follows. Section 1 presents and discusses secondary data about tourism facts and figures, including the economic impact of tourism upon European economies, with a focus on cultural tourism. An extensive review of literature, which identifies the main categories of impacts and the currently available methodologies to assess them, is undertaken. Section 2 focuses on the state of the art. Section 3 describes the database built for the analysis, sources and variables. In order to visually represent the spatial variability of the main parameters, a series of thematic maps at NUTS 3 level(Maps of European tourism), using GIS (Geographical Information System) are also included in the Working Paper. Section 4 shows the results of the econometric analysis of European panel data for the estimation of the effects of tourism specialisation on both local incomes and prices. Section 5 concludes.
Keywords: O4; R0; L83; 330; Cultural Tourism; Economic Growth; Tourismus; Kultur; Makroökonomischer Einfluss; Wirtschaftswachstum; EU-Staaten